Ultrastructural aspects of spermatogenesis in Calyptogena pacifica Dall 1891 (Vesicomyidae; Bivalvia). (26th October 2020) - Yurchenko, Olga V.; Borzykh, Oleg G.; Kalachev, Alexander V.
Abstract: The process of spermatogenesis and spermatozoon morphology was characterized from a deep‐sea bivalve, Calyptogena pacifica (Vesicomyidae, Pliocardiinae), a member of the superfamily Glossoidea, using light and electron microscopy. Spermatogenesis in C . pacifica is generally similar to that in shallow‐water bivalves but, the development of spermatogenic cells in this species has also some distinguishing features. First proacrosomal vesicles are observed in early spermatocytes I. Although, early appearance of proacrosomal vesicles is well known for bivalves, in C . pacifica, these vesicles are associated with electron‐dense material, which is located outside the limiting membrane of the proacrosomal vesicles and disappears in late spermatids. Another feature of spermatogenesis in C . pacifica is the localization of the axoneme and flagellum development. Early spermatogenic cells lack typical flagellum, while in spermatogonia, spermatocytes, and early spermatids, the axoneme is observed in the cytoplasm. In late spermatids, the axoneme is located along the nucleus, and the flagellum is oriented anteriorly. During sperm maturation, the bent flagellum is transformed into the typical posteriorly oriented tail. Spermatozoa of C . pacifica are of ect‐aqua sperm type with a bullet‐like head of about 5.8 μm in length and 1.8 μm in width, consisting of a well‐developed dome‐shaped acrosomal complex, an elongated barrel‐shaped nucleus filled with granular chromatin, and a midpiece with mainly four rounded mitochondria. A comparative analysis has shown a number of common traits in C . pacifica and Neotrapezium sublaevigatum . Abstract : The spermatogenesis in Calyptogena pacifica is similar to that in shallow‐water bivalves. Proacrosomal vesicles are associated with outer electron‐dense material. The axoneme is located near the nucleus until late spermatid stage.